Glosa o interpretacijski diskreciji pri pregonu kaznivega dejanja poslovne goljufije - Keršmanc, Ciril (Pravnik, 2014)
The serious crime of business fraud as defined in the Slovene Penal code is by far the most frequent serious crime in the chapter of economic crime that Slovenian law enforcement and judiciary have to deal with on a daily basis. The central question this article addresses is how to limit the scope of the legal definition to the more serious cases and thus curb overcriminalization, especially vis-a-vis the so called de minimis cases. After briefly outlining the normative development, the author proceeds to classify various (sub)types of business fraud that he encountered during his extensive fieldwork analysis of raw prosecutorial files. The core of the article focuses on two issues in particular that allow for a degree of interpretative discretion in prosecuting and adjudicating cases of this particular crime. Namely, the degree of qualification and concretization of the deception itself and the problem of ex post facto payments in connection to what role such payments should play in assessing whether business fraud was actually committed and if it is worth prosecuting or not.
Keywords: gospodarski kriminal; kazenski postopek; kazniva dejanja; kaznovanje; poslovanje